Responsibility Of The Tual City Government In An Effort To Protect The Copyrights Of Batik Kei Motives - Agustina Balik; Yosia Hetharie; Novyta Uktolseja (Unram Law Review, 2023)
This study aims to identify and analyze the responsibilities of the Tual City government in providing legal protection in the field of intellectual property rights, especially copyright for Batik Kei motifs. This research is socio-legal research, which is a combination research method between doctrinal law research methods and empirical legal research methods. This research was conducted in Tual City, namely the Kei Batik Craftsman with the name Camelia Batik Kei. The types of data in this study are primary data and secondary data obtained through library research and interviews. Based on the results of the research, the Tual City government has an important role in providing copyright legal protection for Camelia Batik Kei's business. But in reality, although the Tual City government often displays Kei Batik motifs which incidentally elevate Kei customs and culture, from the aspect of copyright protection, the government has not given it at all. The entrepreneurs of Camelia Batik Kei are also not very aware of the importance of registering and protecting copyright laws for Kei Batik’s motives. Therefore, there is a need for socialization and cooperation with the local government of Tual City to provide copyright legal protection for Kei batik motifs.